Book Review of The Tyranny of Experts: Economists, Dictators, and the Forgotten Rights of the Poor, by William Easterly - McKenzie, David (Taylor and Francis, 2014)
Journal of Development Effectiveness book reviews review new books on development evaluation and older books from other fields of relevance to our readers. Bill Easterly’s new book is a meandering mélange of anecdotes, parts of Why Nations Fail (Acemoglu and Robinson 2012), and miscellaneous pages from human rights reports, sprinkled with history of economic thought, non sequiturs about one block in New York, finally mixed with some sharper critiques of Thomas Friedman and discussion of the difficulties of measuring the relationship between autocracy and growth.